2009
DOI: 10.1194/jlr.r800076-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

LDL cholesteryl oleate as a predictor for atherosclerosis: evidence from human and animal studies on dietary fat

Abstract: Relationships between dietary fatty acids and blood cholesterol and between blood cholesterol and coronary heart disease (CHD) have been widely documented. Evidence of differential effects of dietary fatty acids on serum cholesterol concentrations was first provided by Kinsell et al. and Groen et al. (1,2), who showed that feeding polyunsaturated fatty acids (PUFA) in the diet lowers total plasma cholesterol compared with saturated fatty acids (SFA). These observations were further supported by ecologic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 39 publications
7
36
0
1
Order By: Relevance
“…Thus, in spite of similar hepatic lipid content, the two different high-fat diets elicited different effects on plasma lipoprotein particles. The results are in line with previous publications [34], and indicate lipid-specific effects (i.e. dependent on lipid source) on hepatic lipid and lipoprotein metabolism.…”
Section: High-fat Diet-mediated Effects On Lipid Profiles and Hepaticsupporting
confidence: 93%
“…Thus, in spite of similar hepatic lipid content, the two different high-fat diets elicited different effects on plasma lipoprotein particles. The results are in line with previous publications [34], and indicate lipid-specific effects (i.e. dependent on lipid source) on hepatic lipid and lipoprotein metabolism.…”
Section: High-fat Diet-mediated Effects On Lipid Profiles and Hepaticsupporting
confidence: 93%
“…LCAT acts primarily on plasma HDL to produce cholesterol linoleate and arachidonate [237] , and for example, in patients with coronary heart disease, the percentage of cholesterol linoleate was found to be diminished [238,239] . This is in agreement with the finding of Degirolamo et al [240] that polyunsaturated fat provide atheroprotection, at least in part, because it limited the accumulation of cholesteryl oleate in favor of cholesteryl linoleate in plasma lipoproteins. In addition, several data suggested that the cholesteryl oleate and cholesteryl palmitate synthesized by ACAT2 are particularly atherogenic [233,235,241] presumably because of the limited ability of macrophages to mobilize cholesterol from these CEs [242] .…”
Section: Factors Affecting Acat1 Upregulation or Downregulationsupporting
confidence: 82%
“…LDL cholesteryl ester fatty acid (CEFA ) composition has been reported to be predictive of atherosclerosis (20)(21)(22). Fig.…”
Section: Mice Diets and Study Outlinementioning
confidence: 99%